Jigsaw Effects on Student Learning Outcomes: A Review - Mubayinah, Siti (Journal of Education Method and Learning Strategy, 2023)
Although cooperative learning strategies provide promise for creating schools that are welcoming to students of all backgrounds, they have not been generally adopted. The Jigsaw system is popular because it is thought to promote students' sociability and learning, and because it seems to be straightforward to apply and follow its four-step teaching framework. A comprehensive assessment of research that has investigated the effects of the Jigsaw method on crucial student educational outcomes was planned and carried out to ensure precise identification of the method's effects. After conducting inductive and deductive topic analyses on 10 Jigsaw studies, three key outcomes emerged: learning (including accomplishment and motivation), social relations, and self-esteem (including academic and social self-esteem). Jigsaw's effects on academic performance (n = 2), motivation (n = 1), social connections (n = 1), and self-perception in the classroom (n = 1) were quantified wherever feasible via supplementary reviews. With the exception of social self-esteem, for which only three studies concluded that the Jigsaw method had positive effects, the primary results of our review focused on the inconsistency of Jigsaw effects and the high degree of variability among studies with regard to all retained student educational outcomes (i.e., achievement, motivation, social relations, and academic self-esteem). Additionally, the findings were consistent across trials. Our analysis sheds light on a number of variables that may account for this variation in research, including sample size, student diversity, and curriculum. The moderating effects of these variables need empirical investigation since they may lead to more effective applications of the Jigsaw technique.